Cuantificación de los volúmenes de desechos que genera la producción bananera en el cantón Santa Rosa - Tamayo Dioses, Angelo Patricio (2013)
The research project Quantification of waste volumes generated by banana production in the canton Santa Rosa was conducted from July to December 2012, with the following objectives:1. Quantify the volumes of waste banana production in the canton Santa Rosa, 2. Develop a computer record and a database of the banana waste classified into two categories and 3. Share the results. 102 farms were selected randomly among semi technologically advanced and technologically advanced, which were visited on different days over six months to complete the process observations fruit packing and record information relating to number of bunches harvested per week, volume discarded fruit waste, rachis weight, use of plastic tape to shore plants, number of bags, Protectors, cravats, cane, type exported carton, boxes Total first processed by farm boxes exported Total, Number of boxes second quality processed and exported, Percentage of fruit for the domestic market, weekly Conversion. The surveys helped collect data from each of the variables and quantify the fate of biodegradable organic waste on farms were selected, which are recorded annually thousands of tons and currently are not handled properly. It was determined that in technologically advanced farms has the highest volume of plastic waste and the semi Technified the largest volume of organic waste. It was concluded that the real possibilities of contamination would lose by applying the laws governing the environment and awareness of farmers about the negative impacts produced by the banana industry, with the adoption of compensatory or mitigation measures.